Aceruloplasminemia presents as Type 1 diabetes in non‐obese adults: a detailed case series. Issue 8 (20th February 2015) - Vroegindeweij, L. H. P.; van der Beek, E. H.; Boon, A. J. W.; Hoogendoorn, M.; Kievit, J. A.; Wilson, J. H. P.; Langendonk, J. G.
Abstract Aim To detect features that might lead to the early diagnosis and treatment of aceruloplasminemia, as initiation of treatment before the onset of neurological symptoms is likely to prevent neurological deterioration. Methods The PubMed and OMIM databases were searched for published cases of aceruloplasminemia. Diagnostic criteria for aceruloplasminemia were undetectable or very low serum ceruloplasmin, hyperferritinemia and low transferrin saturation. Clinical, biochemical and radiological data on the presentation and follow‐up of the cases were extracted and completed through e‐mail contact with all authors. Results We present an overview of 55 aceruloplasminemia cases, including three previously unreported cases. Diabetes mellitus was the first symptom related to aceruloplasminemia in 68.5% of the patients, manifesting at a median age of 38.5 years, and often accompanied by microcytic or normocytic anaemia. The combination preceded neurological symptoms in almost 90% of the neurologically symptomatic patients and was found 12.5 years before the onset of neurological symptoms. Conclusions There is a diagnostic window during which diabetes and anaemia are present although there is an absence of neurological symptoms. Screening for aceruloplasminemia in adult non‐obese individuals presenting with antibody‐negative, insulin‐dependent diabetes mellitus and unexplained anaemia is recommended. The combination of ferritin and transferrin saturation provides a sensitive initial measure for aceruloplasminemia.